Information between hybrid interfaces of technical images - Oliveira, Andréia Machado (PORTO ARTE: Revista de Artes Visuais, 2018)
This article focuses on technical images that pervade our forms of dwelling, feeling, thinking, perceiving and expressing. It aims at reflecting upon today’s expressions of the multiple and its hybrid interfaces under two assumptions: first, that production of multiple images implies, directly or indirectly, understanding technical images that result from emerging technological apparatuses; second, that understanding interfaces requiresan approach to hybrid interfaces that produce images while constituting themselves as images.